The challenges of human management in the IPS of Villavicencio - Laura Camila Cepeda - Dagoberto Torres (GEON Journal (Management, Organizations and Business), 2015)
The Service Institutions of Health in Colombia IPS are responsible to have a direct contact with the patient, hence the importance of having a group of committed and qualified to deliver quality services should work. The different strategies used by IPS help focus staff. This article is based on an interview with German Rodriguez, former manager of the Target Clinic, who to share their management experiences contributes to our purpose to visualize what kind of strategies regarding the management of personnel are used to conduct this type of They assume complex organizations, in addition to constant monitoring by the State and contribute to the implementation and realization of the fundamental right to health. In this article, and as a result of the interview, related professional experience regarding human management to be undertaken by companies in the health sector in view of their characteristics, innovative aspects and situations that helped improve some elements will be found organizational processes.
Keywords: Human management; IPS; Health sector; Customer service; Hiring